The Numerical Analysis of the Hardening Phenomena of the Hot-work Tool Steel. (2017) - Wróbel, Joanna; Kulawik, Adam; Bokota, Adam
Abstract: In the paper, to the numerical analysis of quenching phenomena, the complex model of hardening of the hot-work tool steel is used. The numerical algorithm of the thermal phenomena is based on the solving of the heat transfer equation, which takes into account the heat of phase transformations in the solid state, using the finite element method. Model of estimation of phase fractions and their kinetics is based on the continuous cooling diagram (CCT). Phase fractions which occur during the continuous heating and cooling (austenite, pearlite or bainite) are described by Johnson-Mehl-Avrami (JMA) formula. To determine of the formed martensite the modified Koistinen-Marburger (KM) equation is used. The stress and strain are determined by the solution of the equilibrium equations in the rate form using finite element method. The Young's and tangent modulus were dependent on temperature, whereas the yields stress was function of temperature and phase composition of the hardened element. In the model the thermal, structural, plastic strains and transformation plasticity are taken into account. Thermophysical properties occurring in the constitutive relations depended on the temperature and phase composition of the material. To calculate the plastic strains the Huber-Mises plasticity condition with isotropic hardening is used. Whereas to determine transformations induced plasticity the modified Leblond model is applied. Based on the implemented algorithms of the volumetric hardening process (assuming the various temperatures of the cooling medium) the numerical analysis of the phase content, strains and stresses for the hot-work steel (W360) element is performed.